2014
DOI: 10.1016/j.metabol.2014.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a eucaloric reduced-carbohydrate diet on body composition and fat distribution in women with PCOS

Abstract: Objective To determine if consumption of a reduced-carbohydrate (CHO) diet would result in preferential loss of adipose tissue under eucaloric conditions, and whether changes in adiposity were associated with changes in postprandial insulin concentration. Methods In a crossover-diet intervention, 30 women with PCOS consumed a reduced-CHO diet (41:19:40%energy from CHO:protein:fat) for 8 weeks and a standard diet (55:18:27) for 8 weeks. Body composition by DXA and fat distribution by CT were assessed at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 29 publications
1
37
0
2
Order By: Relevance
“…49,58,74,75 Negative energy balance and PCOS Several studies assessing the effects of caloric restriction along with modified dietary macronutrient composition on multiple health outcomes and biochemical indices have shown that there is no optimal dietary macronutrient composition or dietary pattern for PCOS. 38,41,76 Overall, there is little variation in weight loss with different diets, and this variation may be due to the differences in compliance and not how the body handles different macro-or micronutrients. Negative energy balance (with a deficit of 350-1000 kcal/day) seems to be the key factor leading to successful body weight and fat loss and amelioration of menstrual cycle and insulin sensitivity, irrespectively of the adopted dietary pattern.…”
Section: Lsm Programs and Pcosmentioning
confidence: 99%
See 4 more Smart Citations
“…49,58,74,75 Negative energy balance and PCOS Several studies assessing the effects of caloric restriction along with modified dietary macronutrient composition on multiple health outcomes and biochemical indices have shown that there is no optimal dietary macronutrient composition or dietary pattern for PCOS. 38,41,76 Overall, there is little variation in weight loss with different diets, and this variation may be due to the differences in compliance and not how the body handles different macro-or micronutrients. Negative energy balance (with a deficit of 350-1000 kcal/day) seems to be the key factor leading to successful body weight and fat loss and amelioration of menstrual cycle and insulin sensitivity, irrespectively of the adopted dietary pattern.…”
Section: Lsm Programs and Pcosmentioning
confidence: 99%
“…85 One trial included a diet with <30% carbohydrates, six trials included diets with 40% carbohydrates and four studies with 41-45% carbohydrates. 41,42,76,83,[86][87][88][89][90][91][92] Douglas et al 92 compared the effects of three eucaloric diets: 1) standard (16% protein, 56% carbohydrate, 31% fat), 2) moderately low-carbohydrate (15% protein, 43% carbohydrate, 45% fat) and 3) high monounsaturated fatty acid (MUFA) diets (15% protein, 55% carbohydrate, 33% fat) on glucose and insulin responses in women with PCOS and reported greater reductions in fasting insulin (-3 mIU/L) and lower acute insulin response to glucose (-98 mIU/L × 10 minutes) with the moderately low-carbohydrate diet compared to other two diets. In contrast, results from two clinical trials reported no significant differences in glucose or energy metabolism with moderately low-carbohydrate diets.…”
Section: Dietary Carbohydrates and Pcosmentioning
confidence: 99%
See 3 more Smart Citations